Construction Materials Used in the Historical Roman Era Bath in Myra - Cem Oguz; Fikret Turker; Niyazi Ugur Kockal (The Scientific World Journal)
The physical, chemical, and mechanical properties of mortars and bricks used in the historical building that was erected at Myra within the boundaries of Antalya Province during the Roman time were investigated. The sample picked points were marked on the air photographs and plans of the buildings and samples were photographed. Then petrographic evaluation was made by stereo microscope on the polished surfaces of construction materials (mortar, brick) taken from such historical buildings in laboratory condition. Also, microstructural analyses (SEM/EDX, XRD), physical analyses (unit volume, water absorption by mass, water absorption by volume, specific mass, compacity, and porosity), chemical analyses (acid loss and sieve analysis, salt analyses, pH, protein, fat, pozzolanic activity, and conductivity analyses), and mechanical experiments (compressive strength, point loading test, and tensile strength at bending) were applied and the obtained results were evaluated. It was observed that good adherence was provided between the binder and the aggregate in mortars. It was also detected that bricks have preserved their originality against environmental, atmospheric, and physicochemical effects and their mechanical properties showed that they were produced by appropriate techniques.